Ethics of Justice and Care in Corporate Crisis Management - Simola, Sheldene (Journal of business ethics, 2003)
Despite the importance of ethics in corporate crisis management, they have received limited attention in the academic literature. This article contributes to the evolving conversation on ethics in crisis management by elucidating the ethics of "justice" and "care" and distinguishing between them. Examples of the two approaches are offered through consideration of cases in corporate crisis management, including the alleged glass contamination case faced by Gerber Products Company, and, the shooting tragedy at San Ysidro faced by McDonald's Corporation. It is argued that both an ethic of justice and an ethic of care can be appropriate approaches in corporate crisis management. Areas for future research are discussed.